DETERMINANTS OF FINANCIAL STATEMENTS INTEGRITY IN COMPANY INDEX KOMPAS 100 - Saputri Mashuri, Ayunita Ajengtiyas; Nur Laela Ermaya , Husnah; Fahria, Rahmasari (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
This study aims to empirically examine the effect of independent commissioners, audit committees, KAP size, and intellectual capital, on the integrity of financial statements. This study uses a population of companies with the Kompas 100 index listed on the Indonesia Stock Exchange in the 2018-2021 period. This study uses quantitative methods with data obtained from the company's financial statements and company annual reports or using secondary data. The samples in this study were 40 companies using purposive sampling. The techniques used in analyzing the research data are model specification using multiple regression tests, using the EViews as tools. The results of the study show that (1) independent commissioners have an impact on the integrity of financial statements, (2) the audit committee has no impact on the integrity of financial statements, (3) PAF size has no significant impact on the integrity of financial statements, (4) Intellectual Capital does not have significant impact on the integrity of financial statements.